Are government directors a blessing for actual performance or overvalued by the market? Evidence from China - Yu Wang; Xiaoying Chang; Shanshan Wang (Cogent Business & Management, 2022)
The purpose of this study is to deepen our understanding of government directors' impact on firm performance. This study strives to answer whether government directors have different effects on accounting- and market-based performance. To correct for the endogeneity of government directors caused by self-selection bias, Heckman two-stage model was employed in this study. Using a sample of Chinese publicly listed firms on the Shanghai or Shenzhen Stock Exchanges from 2007 to 2016, the results support our predictions. The results show that government directors are associated with better market-based performance but not finance-based performance, which suggests a discrepancy between the public perspective and the realistic condition. Further, their impact on market-based performance is stronger for firms in high state-monopolized industries, but the results don't hold for finance-based performance. These findings call for more attention on the actual role played by government directors. Previous studies generally tested the impact of government directors on the overall firm performance without differentiating this construct into distinct, meaningful components that reflect firm performance in various domains or aspects. To the best of our knowledge, this is the first study to analyze and examine the differences in government directors' effects on accounting- and market-based performance.
Keywords: 650; accounting-based performance; government directors; industry state monopoly; market-based performance